2012
DOI: 10.1155/2012/914986
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Auditory Neuropathy Caused by Cochlear Nerve Deficiency

Abstract: Objective. To explore possible corelationship between the cochlear nerve deficiency (CND) and unilateral auditory neuropathy (AN). Methods. From a database of 85 patients with unilateral profound sensorineural hearing loss, eight who presented with evoked otoacoustic emissions (EOAEs) or cochlear microphonic (CM) in the affected ear were diagnosed with unilateral AN. Audiological and radiological records in eight patients with unilateral AN were retrospectively reviewed. Results. Eight cases were diagnosed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…We did not restrict our analysis to either the unilateral or bilateral profound HL. A couple of studies have reported AN characteristics in association with CND [14,15]. However, an overall underlying etiologic distribution of AN characteristics could not be drawn since these studies addressed only unilateral cases [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not restrict our analysis to either the unilateral or bilateral profound HL. A couple of studies have reported AN characteristics in association with CND [14,15]. However, an overall underlying etiologic distribution of AN characteristics could not be drawn since these studies addressed only unilateral cases [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies have reported AN characteristics in association with CND [14,15]. However, an overall underlying etiologic distribution of AN characteristics could not be drawn since these studies addressed only unilateral cases [14,15]. To overcome this shortcoming, our current study employed a cohort encompassing both unilateral and bilateral profound HL, consecutively recruited during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 50% were unilateral (all moderate to severe losses). Auditory neuropathy spectrum disorder (ANSD) is unilateral in about 25% of cases (Teagle et al, 2010;Liu et al, 2012). Dedhia et al (2013) investigated a series of 78 children who passed neonatal screening but were subsequently diagnosed with a hearing loss during childhood; 47% were severe or profound and 26% were unilateral.…”
Section: Prevalence/aetiology Of Uhl In Childrenmentioning
confidence: 99%
“…Clemmens et al (2013) assessed 134 children identified with sensorineural UHL using magnetic resonance imaging (MRI) and CT. Cochlear nerve deficiency (CND) was present in 26% overall, but increased to 48% in cases of severe-profound deafness, and 100% in infants (n = 10) and was strongly predicted by narrow (<1.7 mm) BCNC. The clinical presentation of CND overlaps with that of ANSD, and it has become apparent that a high proportion of unilateral ANSD cases are associated with CND (Teagle et al, 2010, Liu et al, 2012.…”
Section: Prevalence/aetiology Of Uhl In Childrenmentioning
confidence: 99%
See 1 more Smart Citation